Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile - Ament, Danilo César (Zootaxa, 2018)
The monotypic genus Hirotophora Brown et al. is revised, with a new species from Chile, Hirotophora chilensis sp. nov., described, and Chaetopleurophora dividua and Chaetopleurophora flavimarginata transferred to this genus. The addition of these species is based on the genus diagnosis, which is amended here, and on the synapomorphies recognized for Hirotophora. All species of the genus are extensively illustrated and new diagnostic characters are described. Females of Hirotophora are more structurally divergent than males, which show almost no conspicuous differences in the male terminalia among the species. This is an uncommon scenario for the subfamily Phorinae, and may relate to still-unknown life history particularities of the species of this genus.